A recent overview of non-classic congenital adrenal hyperplasia due to 21-hydroxylase deficiency: pathophysiology, recognition, and management - Rafał Podgórski; Dominika Podgórska; Marta Sumińska (Termedia Publishing House, 2023)
Congenital adrenal hyperplasia (CAH) is defined as a group of congenital, autosomal, and recessive disorders associated with functional limitations or deficiency of one of the key enzymes in the biosynthesis of steroid hormones leading to hypocortisolaemia and most frequently excessive androgen production. The most common abnormality is associated with 21-hydroxylase deficiency. Activity at the level of 20-70% of normal enzyme function leads to the development of a non-classic form of congenital adrenal hyperplasia (NCAH). In contrast to classic CAH, patients with NCAH manifest normal or partially mild cortisol deficiency and moderate hyperandrogenism without a deficit of mineralocorticoids. Due to nonspecific symptoms, NCAH is often never recognized or is misdiagnosed with polycystic ovary syndrome (PCOS). Recognition can be based on the measurement of 17-hydroxyprogesterone (17OHP) for screening purposes, but the cosyntropin stimulation test with a measurement of 17OHP should be the gold standard. Pharmacological treatment is initiated only in those who manifest significant clinical symptoms.